A critical analysis on the roles of exopolysaccharides and ACC deaminase in salinity stress tolerance in crop plants. (July 2022) - Dutta, Anirudha; Banerjee, Souvik; Dinda, Saheli; Chowdhury, Indranil; Haldar, Srijan; Bandyopadhyay, Subhendu
Abstract: Soil salinity is a big problem in present day agriculture. Salinity diminishes crop productivity which needs immediate solution as there is ever-growing demand for food. Plant scientists are searching for new strategies to combat these stress and in this line rhizosphere engineering using plant growth promoting rhizobiacteria is showing huge promise. In our current article we have critically looked into two main aspects of PGPR strains. Firstly, we have reviewed portrayal of different functions of exopolysaccharides in salinity stress tolerance. Secondly, an in silico study has been performed to attempt structural analysis of ACC Deaminase from different PGPR strains to gain insights for future use.